RING SPINNING MACHINES ON THE INFLUENCE OF THE SHAPE OF THE YARN CARRIERS ON THE DISTRIBUTION AND TENSION OF THE YARN - Quliev T. M.; Jumaniyazov Q.; Djumabaev G. X. (Web of Journals Publishing, 2024)
Thread guides of various shapes have been studied, and among them a thread guide is recommended, which is less affected by changes in the unevenness of the thread as a result of twist spreading.
Keywords: conductors, thread, twist.